Evaluation of the condylar position by conical beam computed tomography in Class III patients undergoing orthognathic surgery - Miranda Villasana, José Ernesto (2020)
Objective. The purpose of this study was to compare the changes by conical beam computed tomography in the condylar positioning of Class III patients before and after a sagittal osteotomy of the bilateral mandibular ramus in Class III indicated for mandibular retroposition. Methods. Thirty patients were analyzed, 16 women and 14 men with an age range of 15 to 40 years and untreated Class III dentofacial deformity who were attended by diagnostic consultation during the period from 2013 to 2016 at the “General Ignacio Zaragoza” Regional Hospital (CDMX, Mexico), performing measurements of the condylar position in three stages: presurgical, intermediate (4 days after surgery) and final (9 months after surgery), in two planes: sagittal section and coronal section. Results. No significant difference was observed in the anterior, central and posterior spaces before (2.56 ± 0.55 mm; 1.78 ± 0.48 mm; 1.92 ± 0.36 mm) and after (2.68 ± 0.51 mm; 1.87 ± 0.43 mm; 2.01 ± 0.37 mm), mean difference -0.120; -0,085; -0.090 p=0.921; 0.948 and 0.778, respectively. Similarly, in the coronal section there are no significant changes in the right condylar angles before (68.25 ± 1.56 °) and after (68.77 ± 1.63°) p=0.217; and left before (68.92 ± 1.63°) and then (69.30 ± 2°) p=0.215. Conclusions. Sagittal osteotomy of the bilateral mandibular ramus in Class III patients is a surgical technique that offers minimal condylar alterations, since it maintains a condylar stability in the postoperative period at 9 months.